Role and Therapeutic Potential of P2X7 Receptor in Lung Cancer Progression - Cao, Yahui; Du, Yanan; Song, Wei; Yu, Qingqing; Wang, Xin; Zhao, Ronglan; Peng, Xiaoxiang (Current Medicinal Chemistry, 2025)
Lung cancer is the second malignant tumor in the world and is the most prevalent malignant tumor of the respiratory system. In lung cancer, the P2X7 receptor (P2X7R) is an important purinergic receptor. P2X7R is a class of ionotropic adenosine triphosphate (ATP)-gated receptors, which exists in many kinds of immune tissues and cells and is involved in tumorigenesis and progression. P2X7R is closely related to lung cancer and is expressed at higher levels in lung cancer than in normal lung tissue. P2X7R plays a critical regulatory function in lung cancer invasion and migration through multiple mechanisms of action and affects the proliferation and apoptosis of cancer cells in the lung. Antagonists of P2X7R can block its function, which in turn has a significant inhibitory effect on lung cancer cell development and progression. This paper details a comprehensive overview of the structure and function of P2X7R. It focuses on the impact and treatment potential of P2X7R in lung cancer invasion, migration, proliferation, and apoptosis, providing new ideas and a new basis for clinical lung cancer treatment and prognosis.
Keywords: ATP